Clinical case report of intrahepatic cholestasis of pregnancy - López Pérez , Grace Pamela (2022)
Introduction: Gestational Intrahepatic Cholestasis (GIC), is considered a dangerous pathology for the fetus, leading to termination of pregnancy, with a high incidence of intrauterine fetal death. Timely treatment reduces symptoms and avoids fetal death. Objective: To compare the signs and symptoms presented in the case report with those presented in the literature review, determining the complications that the fetus may have. Methodology: The methodology used for the analysis of the study comprises a descriptive, comparative design, information was collected by reviewing the patient's clinical history. Results: Based on the analysis, several authors agree that IGC is a condition mainly associated to genetics, not very recurrent, which appears during pregnancy and disappears when it ends, its main symptoms are pruritus in the palms of the hands and feet, in addition to the elevation of bile acids. With a considerable affection towards the fetus and without any subsequent complication for the mother. The pharmacological treatment recommended and used is Ursodeoxycholic. Conclusion: IGC is a complex and potentially dangerous pathology, which compromises maternal-fetal health, and to this day it is still debatable and shows the diversity of criteria to deal with it.